Measuring community development: Perspectives from local government in Western Australia - Saggers, Sherry; Carter, M.; Boyd, S.; Cooper, T.; Sonn, C. (Australian Council of Social Service, 2003)
Local government in Australia has become an important site for discussions about community development and community well being, as increasing numbers of community services are being devolved to this level. Pressures towards greater accountability and demonstration of competitiveness, stemming from the implementation of National Competition Policy have led to attempts to better measure community development activities. In this paper we report on research conducted among management, elected members and community workers at five Western Australian Local Government Authorities which explored the nature and appropriateness of community development measurement. We found workers at all levels of employment struggling, not simply with notions of measurement, but also with fundamental understandings of community development.